Case Report: Duodenal Carcinoma in a 40-Year-Old Asian Man With Cowden Syndrome - Zhao, Mingkun; Lin, Xiaohan; Fang, Yuan; Zhuang, Aobo; Tong, Hanxing; Lu, Weiqi; Zhou, Yuhong; Zhang, Yong (Frontiers in Surgery, 2022)
Introduction Cowden syndrome is a rare autosomal dominant genetic disease associated with PTEN mutation and is mainly shown as systemic multisystem lesions. The incidence of adenocarcinoma of the duodenum with Cowden syndrome in Asian males is rare. We hereby describe the diagnosis, treatment, and prognosis of a patient with duodenal carcinoma and Cowden syndrome. Case Description A 40-year-old Chinese man was hospitalized because of gastrointestinal hemorrhage and anemia due to infiltrating adenocarcinoma of the descending part of the duodenum. He also had typical signs of Cowden syndrome, such as multiple polyps of the gastrointestinal tract, macrocephaly, papilloma of the tongue, soles hyperkeratosis, and melanosis spots. After the pancreaticoduodenectomy (classic Whipple), the lesions revealed the presence of hamartomatoid polyps, and some of them mutated into non-mucinous adenocarcinoma (80%) and mucinous adenocarcinoma (20%). Further investigation showed a lack of PTEN protein expression in the duodenal neoplasm, and genetic analysis showed the mutation of p.E242fs in PTEN. The patient was followed up for 1 year. There was no appearance of recurrence or distant metastasis. Conclusion It is suggested that we should pay more attention to the differential diagnosis of duodenal carcinoma combined with gastrointestinal polyps. If multiple gastrointestinal polyps with gastrointestinal bleeding are encountered, Cowden syndrome should be considered, and timely diagnosis and treatment should be implemented.